Bilateral combined resection-recession of the same rectus muscle versus Fadenoperation for treatment of purely tonic esotropias. Issue 2 (March 2022) - Fremont, Félix; Thouvenin, Dominique
Purpose: To compare the efficiency of bilateral combined resection-recession surgery of the medial rectus muscle versus using a modified Fadenoperation for surgical management of esotropias that totally resolve under general anesthesia, which we called "purely tonic" esotropias. Methods: We included 65 unselected consecutive cases of patients with purely tonic esotropias who underwent surgery between October 2017 and 2018. Patients were divided into group I, who underwent a combined resection and recession of medial recti muscles, and group II, who underwent a bilateral medial rectus Fadenoperation using posterior strapping. A satisfactory outcome was defined as deviation ⩽10 prism diopters (PD), at near and distance fixation, between 3 and 6 months postoperatively. Results: Mean initial deviation was in group I, 19.6 PD and 32.0 PD, in group II, 23.6 PD and 33.5 PD, at distance and near fixation respectively. Postoperatively, in group I, 31 patients (91.2%) showed satisfactory alignment at near and distance fixation. Post-operatively, in group II, 25 patients (80.6%) showed satisfactory alignment at near and distance fixation. Conclusion: Our results suggest both techniques are good options to treat purely tonic esotropias.